Trace amount Pt anchored on nitrogen-doped carbon nanoparticle with hollow capsule structure for efficient electrocatalytic oxygen reduction - Xiaojun Zhao; Shi Wang; Qiujuan Zhang; Yonghui Lin; Weiting Yang; Yan Chen; Qinhe Pan (International Journal of Thermofluids, 2023)
The utilization of sustainable green energies requires the energy conversion devices to enhance the convenience of use and storage. The oxygen reduction reaction (ORR), as one of the necessary steps in the operation of these devices, exhibits a slow reaction kinetic rate that seriously affects energy conversion and output efficiency. Due to the low abundance and poor stability of Pt, it is essential to develop high-performance oxygen reduction catalysts with low Pt loading. In this work, a composite precursor consisting of ZIF-8 coupled with ferrocene and chloroplatinic acid was prepared, and subsequently derived to obtain nitrogen-doped carbon nanoparticles with hollow capsule morphology on the surface. These hollow capsule structure formed with the assistance of Pt and Fe significantly enhances the performance of Pt/FC@ZIF-8-C nanoparticles as the ORR electrocatalyst, exhibiting superior catalytic activity and stability compared to Pt/C at a low Pt loading (0.7 wt%). This is very important for promoting the design and preparation of Pt-based catalysts, as well as the application of energy conversion and storage devices in the field of green energy sources.